Taboo Words In The Bajo Language: An Ethnosemantic Study Of The Adonara Island Bajo Community - Ubaldus Djonda; Elvis Albertus Bin Toni (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
This study examines taboo language in the Bajo community of Adonara Island, Indonesia, with a focus on its meanings and sociocultural functions. Taboo expressions (pemali) represent culturally prohibited forms of speech associated with moral values, social norms, and traditional beliefs. Despite extensive studies on taboo language in other Indonesian contexts, research on the Bajo language remains limited, particularly from an ethnosemantic perspective. This study aims to fill that gap by analyzing the meanings of taboo expressions used by Bajo speakers and exploring their cultural significance. A qualitative research design was employed, with data collected through observation, elicitation, and in-depth interviews involving native Bajo speakers and community leaders in Meko Hamlet, Adonara Island. The data were analyzed by identifying, classifying, and interpreting taboo expressions based on their semantic and cultural meanings. The findings reveal 22 taboo expressions categorized into three main groups: body-part-related taboos, animal-based taboos, and direct insulting expressions. These expressions operate on denotative, connotative, and symbolic levels. Beyond their literal meanings, they function as mechanisms for expressing emotions, enforcing social norms, and protecting personal and family honor. The study also highlights a generational shift, where younger speakers show limited understanding of the cultural values embedded in taboo language.This research contributes to the fields of linguistics and linguistic anthropology by demonstrating the role of taboo language as a reflection of cultural identity and social regulation. It also underscores the importance of preserving local linguistic traditions in the face of changing social dynamics.